Adult smokers' reactions to pictorial health warning labels on cigarette packs in thailand and moderating effects of type of cigarette smoked: Findings from the international tobacco control southeast asia survey - Hua Hie Yong (2018)
In this study, we aimed to examine, in Thailand, the impact on smokers' reported awareness of and their cognitive and behavioral reactions following the change from text-only to pictorial warnings printed on cigarette packs. We also sought to explore differences by type of cigarette smoked (roll-your-own [RYO] vs. factory-made [FM] cigarettes). Data came from the International Tobacco Control Southeast Asia Survey, conducted in Thailand and Malaysia, where a representative sample of 2,000 adult smokers from each country were recruited and followed up. We analyzed data from one wave before (Wave 1) and two waves after the implementation of the new pictorial warnings (two sets introduced at Waves 2 and 3, respectively) in Thailand, with Malaysia, having text-only warnings, serving as a control. Following the warning label change in Thailand, smokers' reported awareness and their cognitive and behavioral reactions increased markedly, with the cognitive and behavioral effects sustained at the next follow-up. By contrast, no significant change was observed in Malaysia over the same period. Compared to smokers who smoke any FM cigarettes, smokers of only RYO cigarettes reported a lower salience but greater cognitive reactions to the new pictorial warnings. The new Thai pictorial health warning labels have led to a greater impact than the text-only warning labels, and refreshing the pictorial images may have helped sustain effects. This finding provides strong support for introducing pictorial warning labels in low- and middle-income countries, where the benefits may be even greater, given the lower literacy rates and generally lower levels of readily available health information on the risks of smoking. © The Author 2013. Published by Oxford University Press on behalf of the Society for Research on Nicotine and Tobacco.